Ibn al ʿArabi's Philosophy and Sufism: Impact on Moroccan Contemporary Thought (Philosophy and Progress, 2025)
The paper explores the influence and impacts of Ibn al Arabi’s philosophy and Sufism on the contemporary Moroccan thought. To achieve that, a few key doctrines and messages of Ibn al ʿArabi have been highlighted in the first few sections, and then a brief literature survey was conducted for relevant thinkers, Sufis and writers of Morocco and greater world, some such names have been listed and specified in the paper. Also, few interviews of writers, professors and intellectuals were conducted by the author and visits took place to libraries, historical Ibn al ʿArabi specific sites. It was found that, at least seven Moroccan sages and spiritual writers maintained Ibn al ʿArabi’s legacy from the 13th to the 19th century. Also, on Moroccan Contemporary Thought, a brief study and investigation of modern writers, authors, publishers and music bands in Morocco and neighbouring countries, reveal a direct influence of Ibn al ʿArabi and his messages in writings, songs, in prayers and ritual practices. The trend showed the progressive adoption of the principles of Universal Humanism and Religious Diversity, which were the key doctrines and messages propagated by Ibn al ʿArabi in his prolific writings. A brief study and review of 55 books and articles, reveal that majority of those writers were found to be Moroccan who wrote during the present century and the last centuries. Amongst the majority of books and articles reviewed, it was found that almost 80% were written on Sufism mentioning the aspects of Ibn al ‘Arabi’s teaching, and approximately 20% of those books were written on contemporary philosophical topics proposed by Ibn al ʿArabi. From the interviews of professors and academic scholars, it was found that many prominent Moroccan universities have been conducting research on Ibn al ʿArabi. Also based on findings, the article discovered the opinion that the Morocco’s state-based support to Sufism, which is currently part of its religious identity, emphasizing its role in promoting moderation and tolerance, especially in the 2011 constitution commitment to religious and cultural diversity, indicates an influence of Ibn al ʿArabi and other similar Sufi thinkers of the Muslim world. Finally, the article concludes that Ibn ‘Arabi’s legacy is fully alive in Morocco even as of today. The influence and impact of Ibn al ʿArabi on the Moroccan Contemporary Thought is fully prevalent, mostly in Sufis and Philosophers circles.Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 279-307